2001
DOI: 10.1007/s100670170023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Selected Disease Activity Markers in Patients with Systemic Lupus Erythematosus

Abstract: The objective of this study was to assess the utility of measurement of thrombomodulin, antinucleosome antibodies, sVCAM-1, sICAM-1, neopterin, fas ligand, IL-10 and sIL-2R in patients with systemic lupus erythematosus (SLE) and to compare them with traditional markers of SLE activity (anti-dsDNA antibodies, C3, C4) and the ECLAM index of disease activity. The measurement was performed over a 6-month period at three consecutive time points after 3 months in each of the 52 patients with SLE. Anti-dsDNA antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
(36 reference statements)
5
26
0
1
Order By: Relevance
“…Elevated levels of neopterin have been observed in association with several autoimmune diseases. [53][54][55][56] CRP is an acute-phase protein that is secreted by hepatocytes and is thought to modulate inflammatory responses, although the exact mechanism remains unclear; serum levels of CRP are often elevated among patients with acute RF. 8,57 Therefore, it was of interest to determine the relationships between neuropsychiatric diseases and neopterin and CRP levels in serum derived from patients and control subjects.…”
Section: Nonspecific Markers Of Immune Activationmentioning
confidence: 99%
“…Elevated levels of neopterin have been observed in association with several autoimmune diseases. [53][54][55][56] CRP is an acute-phase protein that is secreted by hepatocytes and is thought to modulate inflammatory responses, although the exact mechanism remains unclear; serum levels of CRP are often elevated among patients with acute RF. 8,57 Therefore, it was of interest to determine the relationships between neuropsychiatric diseases and neopterin and CRP levels in serum derived from patients and control subjects.…”
Section: Nonspecific Markers Of Immune Activationmentioning
confidence: 99%
“…Its soluble form can be detected in the plasma and urine after endothelial cell injury. All studies found elevated levels of soluble thrombomodulin in patients with active SLE, especially those with nephritis [48,49,[55][56][57]. The consistent results observed in all studies make soluble thrombomodulin a good candidate as a biomarker of disease activity, especially in patients with lupus nephritis.…”
Section: Markers Of Endothelial Activationmentioning
confidence: 55%
“…Markers of endothelial activation are, therefore, attractive candidates as biomarkers of disease activity. Soluble vascular cell adhesion molecule-1 (sVCAM-1) levels are elevated in patients with active lupus and correlate with global measures of disease activity [48][49][50][51][52][53]. In some studies the correlation was stronger for those who had renal disease than those who only had extrarenal disease syndrome [48,50,54].…”
Section: Markers Of Endothelial Activationmentioning
confidence: 97%
“…Such levels of neopterin have been observed in association with several auto-immune diseases and suggest a challenge to the immune mechanisms. However, this does not specifically indicate either a streptococcal infection or an auto-immune reaction (Altindag, Sahin, Inanici, & Hascelik, 1998;Berdowska & Zwirska-Korczala, 2001;Giovannoni et al, 1997;Horak et al, 2001).…”
Section: Resultsmentioning
confidence: 81%